SOSIALISASI KAMPANYE POLITIK MELALUI MEDIA DI KOTA TANJUNGPINANG - Nur Aslamaturrahmah Dwi Putri; Yudhanto Satyagraha Adiputra (Universitas Lancang Kuning, 2018)
Indonesia has experienced a fairly rapid development in terms of democracy. Changes in the way in democracy affect the implementation of democracy itself. Conventional democracy that is usually used slowly changes but not as a whole becomes digital democracy. The dimensions of a digital democracy are the dimensions of the campaign which is one of the sequences that must be passed by the candidate pair during the democratic party, namely the election. Political campaigns that used to spend huge amounts of money because they were carried out conventionally turned to political campaigns with quite cheap costs, namely by using social media. But in its implementation the interactions that occurred during the campaign on social media took place very intensely but many were charged with violations, namely hoaxes, hate speech and containing elements of sara. This is due to the lack of public knowledge of the mechanisms and rules for campaigning on social media. So it is very necessary to hold community service activities in the form of socialization in order to increase public knowledge so as not to be ensnared by law in the current political years. With the hope that the community will be wiser in interacting on social media and conducive conditions in a regional head election or presidential election can be achieved. Keywords :socialization, politic campaign, social media